Literature in efL: beyond language learning - Rincón, Luis Jesús (Colombian Applied Linguistics Journal, 2013)
This article presents the results of a qualitative research which looks into the field of literature in EFL. Seventh grade students of a private school in Bogota took part in the research. Data was collected by means of audio recordings of small group discussions, teacher´s journal, and responses to literature logs. The results show that the connections that EFL learners make with literary texts enrich their interpretations, analysis and value judgments of experiences and real life events. Furthermore, critical thinking skills are potentiated. In addition to this, literary texts bring up appealing and meaningful topics in the classroom enhancing students´ motivation and willingness to use the target language.